The Needs Analysis For Designing ESP Materials For Multimedia Department at Vocational High school - Dhiyoulhaq, Nabiel; Fitriyah, Siti Masrifatul; Puspas, Areta (EFL Education Journal, 2023)
This research was categorized as a case study design. The purpose of this research was to to provide data dealing with ESP materials for students of multimedia department at vocational high school using Helen Basturkmen (2010) principles.. The area of this research was SMK Islam Bustanul Ulum Jember. The population of this research was the multimedia department especially MMD 5 of eleventh grade students at SMK Islam Bustanul Ulum Jember. In this research, questionnaire and interview were used to get the data each from the students, the English teacher, and the vocational teacher. Based on two research main data source which are need analysis questionnaires and semi-structured interview, it is conluded that ESP materials for multimedia department are significantly needed. Contrary, the amount of desired materials are limited. It is supported by the statement of the English teacher who argued that both the government and school only provied EGP for vocational high school students which is inappropriate. Therefore, the data collected from this research may store some important informations needed by the future researchers which share the same interest.